Pengaruh Jenis Mulsa Organik dan Takaran Kompos Biochar terhadap Pertumbuhan dan Hasil Kacang Tunggak (Vigna unguiculata L. subsp. unguiculata) dalam Tumpangsari di Lahan Kering - Stefanus Tahoni (Savana Cendana, 2021)
This study aims to determine the effect of the type of organic mulch and the dose of biochar compost on the growth and yield of cowpeas (Vigna unguiculata L. subsp. Unguiculata) in intercropping on dry land. It was carried out from March 2018 to September 2018. The place for the research was carried out in the experimental garden of the Faculty of Agriculture, University of Timor, Sasi Village, Kefamenanu City District, North Central Timor Regency. Using a plot with 2 faktorial plots of organic mulch consisting of 3 levels, namely: no mulch, Reed mulch, corn straw mulch, the second faktor is the compost dosage which consists of 4 levels, namely: without fertilizer 0 t/Ha, 1 t/Ha, 2.5 t/Ha, 5 t/Ha, combination, the treatment is 3 times so that there are 36 experimental units. The results of the ANOVA variety showed that there was no interaction effect between the type of mulch treatment and the dose of biochar compost on the growth parameters of plant height, number of leaves, and stem diameter. The results showed that the observation of plant height growth, soil treated with 5 t/Ha biochar compost and Imperata mulch gave the best results. The average research results obtained from growth observations, a biochar compost dose of 10 t/Ha combined with alang-alang mulch treatment provided optimal growth for cowpea plants.